2021
DOI: 10.1096/fj.202100800r
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant accumulation of TMEM43 accompanied by perturbed transmural gene expression in arrhythmogenic cardiomyopathy

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In human patients, mutations in the nuclear envelope protein TMEM43 are responsible for severe diseases, including ACM type 5, a devastating cardiomyopathy that causes malignant arrhythmias and heart failure [ 18 , 26 , 27 ]. Despite efforts in recent in vivo studies using transgenic, knock-in, or knock-out rodent models, the pathogenic mechanisms of TMEM43-associated ACM remain still poorly understood [ 22 , 30 , 31 , 32 , 33 , 34 ]. In this study, we generated the first transgenic zebrafish model expressing two different potential pathogenic variants found in human patients under a heart-specific promoter and generated genetic mutants of tmem43 in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In human patients, mutations in the nuclear envelope protein TMEM43 are responsible for severe diseases, including ACM type 5, a devastating cardiomyopathy that causes malignant arrhythmias and heart failure [ 18 , 26 , 27 ]. Despite efforts in recent in vivo studies using transgenic, knock-in, or knock-out rodent models, the pathogenic mechanisms of TMEM43-associated ACM remain still poorly understood [ 22 , 30 , 31 , 32 , 33 , 34 ]. In this study, we generated the first transgenic zebrafish model expressing two different potential pathogenic variants found in human patients under a heart-specific promoter and generated genetic mutants of tmem43 in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that already slight changes in energetics may affect the conformational stability [ 44 ]. Although, the substitution of serine to leucine might have only a minor effect on energetics, it might be sufficient to impair correct membrane topology of TMEM43, resulting in a disturbed ability to interact with other nuclear envelope or LINC complex proteins [ 22 ]. Furthermore, distorted TMEM43 appears to be destabilized, which is illustrated by the partial redistribution of TMEM43-p.S358L to the cytoplasm ( Figure 2 D,E).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this activation does not promote a typical cardiac inflammatory response, instead leading to TGFβ-mediated fibrosis [ 105 ]. On the other side, inflammatory cell infiltration was also observed in homozygous Tmem43-S358L KI rats [ 106 ]. Consistently, GSK3β inhibition in TMEM43 mutant mice resulted in a relative improvement in the contractile function [ 105 , 141 ].…”
Section: Modeling Myocardial Inflammation In Cardiomyopathies: Eviden...mentioning
confidence: 99%